Bioavailability of dissolved organic nitrogen (DON) in wastewaters from animal feedlots and storage lagoons. (November 2017) - Sun, Jingyi; Khan, Eakalak; Simsek, Senay; Ohm, Jae-Bom; Simsek, Halis
Abstract: Dissolved organic nitrogen (DON) from animal wastes can contribute to pollution of surface waters. Bioavailable DON (ABDON) is a portion of DON utilized by algae with or without bacteria. This study determined DON and ABDON levels in animal wastewater collected from two different sources: an animal feedlot wastewater storage tank and a sheep wastewater storage lagoon. Inocula for the ABDON bioassays were comprised of individual species and several combinations involving two algae ( Chlamydomonas reinhardtii and Chlorella vulgaris ) and a mixed liquor suspended solids (MLSS) bacterial culture. The ratio of initial DON to initial total dissolved nitrogen was 18% in the feedlot wastewater samples and 70% in the lagoon wastewater samples. The results showed that between 1.6 and 4.5 mg-NL-1 DON (45–79% of initial DON) in the feedlot samples and between 3.4 and 7.5 mg-NL-1 DON (36%–79% of initial DON) in the lagoon samples were bioavailable with the inocula tested. These results suggest that when considering eutrophication potential of livestock wastewater, organic nitrogen should be included in addition to the obvious culprits, ammonia and nitrate. Graphical abstract: Highlights: Bioavailability of DON in livestock wastewaters is similar regardless of wastewater sources. Between 36 and 79% of DON in livestock wastewaters is bioavailable to either algae or algae + bacteria inoculum. A portion of DON is nonbioavailable to algae and/or bacteria inoculum. Algae + bacteria inoculum provides conservative DON bioavailability prediction.